Kontekstualisasi Nilai-nilai Pendidikan Islam dalam Sejarah Keemasan Islam - Nur Novi Yana; Miftahul Jannah; Mahfud Ifendi (PT PUSTAKA CENDEKIA GROUP, 2024)
The Islamic Golden Age (750-1258 CE) was a pivotal period in the history of Islamic civilization, marked by significant advancements in various fields, including education. The educational values of this era were rooted in the principles of the Qur'an and Hadith, promoting the integration of religious and general sciences. This study aims to contextualize the educational values of the Golden Age into contemporary education systems. A qualitative research method based on literature review was employed to explore the contributions of figures such as Al-Farabi, Ibn Sina, and Al-Ghazali, as well as institutions like madrasahs and the House of Wisdom. The findings reveal that principles of knowledge integration, ethics, and character development can serve as a foundation for modern educational reform. Moreover, applying these values enables the formation of a holistic educational system that is relevant to contemporary challenges while remaining rooted in Islamic traditions.